Exercise ameliorates the FGF21–adiponectin axis impairment in diet-induced obese mice. Issue 5 (May 2019) - Yang, Wenqi; Liu, Ling; Wei, Yuan; Fang, Chunlu; Zhou, Fu; Chen, Jinbao; Han, Qinghua; Huang, Meifang; Tan, Xuan; Liu, Qiuyue; Pan, Qiang; Zhang, Lu; et al.
Abstract : Objective: The protective effects of exercise against glucose dysmetabolism have been generally reported. However, the mechanism by which exercise improves glucose homeostasis remains poorly understood. The FGF21–adiponectin axis participates in the regulation of glucose metabolism. Elevated levels of FGF21 and decreased levels of adiponectin in obesity indicate FGF21–adiponectin axis dysfunction. Hence, we investigated whether exercise could improve the FGF21–adiponectin axis impairment and ameliorate disturbed glucose metabolism in diet-induced obese mice. Methods: Eight-week-old C57BL/6J mice were randomly assigned to three groups: low-fat diet control group, high-fat diet group and high-fat diet plus exercise group. Glucose metabolic parameters, the ability of FGF21 to induce adiponectin, FGF21 receptors and co-receptor levels and adipose tissue inflammation were evaluated after 12 weeks of intervention. Results: Exercise training led to reduced levels of fasting blood glucose and insulin, improved glucose tolerance and better insulin sensitivity in high-fat diet-induced obese mice. Although serum FGF21 levels were not significantly changed, both total and high-molecular-weight adiponectin concentrations were markedly enhanced by exercise. Importantly, exercise protected against high-fat diet-induced impaired ability of FGF21 to stimulate adiponectin secretion. FGF21 co-receptor, β-klotho, as well as receptors, FGFR1 and FGFR2, were upregulated by exercise. We also found that exercise inhibited adipose tissue inflammation, which may contribute to the improvement in the FGF21–adiponectin axis impairment. Conclusions: Our data indicate exercise protects against high-fat diet-induced FGF21–adiponectin axis impairment, and may thereby exert beneficial effects on glucose metabolism.